Australian community pharmacists’ experiences during the COVID-19 pandemic - Kanaani, Eman; Salahudeen, Mohammed S; Curtain, Colin (The International journal of pharmacy practice, 2023)
Abstract Objectives Community pharmacists have played an important role in providing services for their community during the COVID-19 pandemic. In this study, the purpose is to present the attitudes and experiences of Australian pharmacists regarding the COVID-19 pandemic. Methods A qualitative semi-structured interview explored community pharmacist experiences during the initial COVID-19 lockdown. Thematic analysis of transcribed interviews was conducted to investigate the experiences of pharmacists. Key Findings Interviews were conducted with 15 pharmacists from different regional areas and states of Australia. In the study, five main themes were developed: COVID-19 practice complications; pharmacy practice changes; difficult patient interactions; worsened mental well-being and coping strategies; and career dissatisfaction. Pharmacists stated that an increase in workload, shortage of supplies and frequent COVID-19 management updates increased pressure on their duties. The negative customer interactions during COVID-19 lockdown adversely affected some pharmacists’ mental health and career satisfaction. Conclusions Community pharmacists are subject to multiple factors affecting their practice, impairing their mental well-being and triggering them to reconsider their career choice. It is important to provide support to community pharmacists to help improve their well-being and workplace satisfaction.